An ecological approach to understanding the impact of sexual violence: a systematic meta-review - Stockman, Dagmar; Haney, Laura; Uzieblo, Kasia; Littleton, Heather; Keygnaert, Ines; Lemmens, Gilbert; Verhofstadt, Lesley (Frontiers in Psychology, 2023)
Aim: A systematic meta-review was conducted to examine (1) the broad range of negative and positive individual and interpersonal changes following adult sexual violence, as well as (2) the risk/protective factors at multiple levels of the social ecology (e.g., individual, assault, and micro/meso/exo/macro/chronosystem factors) - influencing the impact of sexual violence. Methods: Searches of Web of Science, Pubmed and ProQuest resulted in inclusion of 46 systematic reviews or meta-analyses. Review findings were extracted for summary and a deductive thematic analysis was conducted. Results: Experiencing sexual violence is associated with many negative individual and sexual difficulties as well as revictimization risk. Only a limited number of reviews reported on interpersonal and positive changes. Factors at multiple levels of the social ecology play a role in the intensity of these changes. Reviews including macrolevel factors were non-existent, however. Conclusion: Reviews on sexual violence are fragmented in nature. Although the use of an ecological approach is often lacking, adopting such a perspective in research is necessary for a fuller understanding of the multiple influences on survivor outcomes. Future research should evaluate the occurrence of social and positive changes following sexual violence, as well as the role of macrolevel factors in influencing post-assault outcomes.